Analysis on flow structure in a vortex pump under all flow rates - Minggao Tan; Kaiyao Zhao; Xianfang Wu; Houlin Liu; Chen Shao; Bo Pan (Water Supply, 2023)
Vortex pumps are usually designed based on its inner flow model. Currently, the flow models of vortex pump just consider flow rate at the design condition, which results in low efficiency under off-design flow rates in practical engineering. Therefore, the main objective of this article is to build a flow model that takes into account the impact of flow rates. To reveal the flow mechanism of vortex pump, we provide refined flow field simulations for a vortex pump. Performance experiments were conducted to validate the numerical simulation method. The study found that the vortex structure in the non-blade cavity can be regarded as a Rankine-like vortex. The inflow range is limited to the hub diameter (45 mm), smaller than the volute inlet diameter (85 mm). The action radius of the forced vortex gradually decreases from the impeller side to the inlet side. The maximum radius of the forced vortex on the impeller side is determined by the impeller diameter. As the flow rate increases, the action radius of the forced vortex on the inlet side gradually increases, while the axial length of the vortex in the inlet pipe gradually decreases. Based on the study of internal flow, a new flow model is proposed. HIGHLIGHTS The vortex structure in the non-blade cavity could be regarded as a kind of Rankine-like vortex.; The relationship between flow structure and physical parameters was established.; A more accurate and comprehensive flow model of the vortex pump was established.;